(untitled) (Research, Society and Development, 2021)
Introduction: Esthetics dental treatments involving ceramic laminate veneers can obtain optimal results through detailed considerations with respect to teeth preparations, gingival margins and esthetic factors. Objectives: This case report aims to present a conservative management for ceramic conservative preparation associated with the digital workflow for ceramic laminates, with 18-month follow-up. Case Report: Patient complaining of a child smile due to diastemas in the anterior region. The planning and design of the smile was carried out using a software (Keynote, Ceramill Mind). After molding and printing a 3D model, a mock-up was performed, which was used as a surgical guide for the performance of gingivoplasty. The conservative dental preparation was then performed, with cervical enamel preservation. The ceramic laminates were made after molding and scanning the model, using the CAD/CAM system and cemented on the dental surface. It was observed that there was an increase in gingival quality and thickness, achieving esthetics, color and marginal stability, after 18 months of follow-up. Conclusion: The conservative preparation technique associated with the digital workflow allowed the manufacture of thin ceramic laminate veneer, promoting stability of esthetics and periodontal health after 18 months.